Insulin-loaded composite nanoparticles as well as preparation method and application thereof

By designing insulin-loaded composite nanoparticles, using core-shell structures and multi-layer shell structures, the problems of low bioavailability of oral insulin and inability to intelligently regulate insulin release are solved, and efficient blood sugar regulation and long-term insulin effect are achieved.

CN119909037APending Publication Date: 2025-05-02HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510105106.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, oral insulin has low bioavailability, cannot intelligently regulate insulin release, and it is difficult to maintain dynamic balance of blood sugar in the body.

Method used

A complex nanoparticle loaded with insulin was designed, using a core-shell structure, in which the core is a polyelectrolyte complex formed by self-assembly of L-valine-modified chitosan and insulin, and the shell is an anionic polysaccharide, such as fucose gum. Through layer-by-layer adsorption, a multi-layer shell structure is formed outside the polyelectrolyte complex, including L-valine modified chitosan and fucose gum, to improve the stability and intestinal targeting of the nanoparticles.

Benefits of technology

It improves the oral bioavailability of insulin, extends the time of insulin in the body, realizes intelligent regulation of blood sugar levels, reduces blood sugar fluctuations, and significantly improves the quality of life of diabetic patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909037A_ABST
    Figure CN119909037A_ABST
Patent Text Reader

Abstract

The invention discloses an insulin-loaded composite nanoparticle and a preparation method and application thereof, the composite nanoparticle has a core-shell structure, the core is a polyelectrolyte complex formed by self-assembly of L-valine modified chitosan and insulin, and the shell is anionic polysaccharide; or the composite nanoparticle has a multi-layer core-shell structure, the core is a polyelectrolyte complex formed by self-assembling phenylboronic acid modified gelatin and insulin, and two layers of shells, namely L-valine modified chitosan and fucoidan, are formed outside. The pharmaceutical composition can be used for oral administration and injection administration for treating diabetes mellitus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical composite nanoparticles, in particular to composite nanoparticles loaded with insulin and a preparation method and application thereof. Background Art

[0002] Diabetes is a metabolic disease characterized by high blood sugar, which is caused by defects in insulin secretion, impaired action, genetics, environment, etc. It is the third most serious chronic non-communicable disease that endangers human health after tumors and cardiovascular and cerebrovascular diseases. At present, the only way to use insulin clinically is subcutaneous injection. Although it has a rapid onset and high bioavailability, long-term injection brings great pain, inconvenience and poor compliance to patients, and is often accompanied by complications. Therefore, in order to meet the needs of diabetic patients, prolong the action time of insulin in the body, and better treat diabetes, the development of non-injection administration routes has become a research hotspot. Oral administration is the safest and most convenient, and patient compliance is the best. Its biggest advantage is that it avoids complications at the administration site. However, for insulin, direct oral administration faces the strong acid effect of gastric acid and the degradation of proteases. Moreover, as a biological macromolecule, insulin is difficult to cross the intestinal epithelial barrier. Therefore, direct oral administration of insulin cannot produce biological activity to lower blood sugar.

[0003] Nano drug carriers are a new type of drug delivery system. Encapsulating insulin in nano carriers can protect insulin to a certain extent and prevent it from being degraded by strong acids and various enzymes in the gastrointestinal tract. Organic polymers and inorganic nano carriers can be used as carriers for oral delivery of insulin, such as natural polymers, synthetic polymers, inorganic metal ions, liposomes, etc. Nano carriers encapsulate insulin, which can not only effectively protect insulin and improve its stability, but also promote the gastrointestinal tract to take up insulin and improve its oral bioavailability.

[0004] As natural biomaterials, polysaccharides are widely present in nature and are relatively easy to obtain. They are safe, non-toxic, biodegradable, and have good biocompatibility. In addition, some polysaccharides have excellent biological activity and adhesion properties and can interact with cell receptors. Therefore, polysaccharide-based nanodrug carriers are considered to be an important and reliable technical strategy to protect insulin from being decomposed by various enzymes in the gastrointestinal tract and to promote the transport and absorption of insulin through transcellular or cell-bypass pathways. In addition, specific functional groups in the polysaccharide structure can be modified by physical, chemical or enzymatic methods to adjust their functions to achieve different purposes.

[0005] Chitosan is a linear aminopolysaccharide obtained by deacetylation of chitin extracted from the exoskeleton of natural crustaceans. Structurally, chitosan is a cationic polysaccharide composed of repeating 2-amino-2-deoxy-d-pyranose and 2-acetylamino-2-deoxy-d-pyranose units. The hydroxyl and amino groups on the chitosan backbone provide ample opportunities for various chemical modifications, which makes chitosan have great functional potential. Due to its biodegradable properties and the lack of obvious toxic effects in both in vitro and in vivo studies, chitosan has been approved by the US Food and Drug Administration (FDA) for use in tissue engineering.

[0006] The small intestine is the main absorption site of the nano drug delivery system. The main factors affecting the intestinal absorption of insulin nano drug delivery systems include the particle size, zeta potential, morphology, surface properties of the nanocarrier, as well as the properties of the polymer molecular weight, viscosity, charge, etc. Studies have shown that the uptake of nanoparticles by intestinal cells or M cells is related to the size of the particle size. Intestinal cells can absorb small particles, while M cells are more likely to absorb larger particles. Nanocarriers with positive charges or hydrophobic surfaces are conducive to the endocytosis of intestinal epithelial cells. However, in fact, the absorption of these cationic or hydrophobic nanoparticles is very limited because they must pass through the glycocalyx and negatively charged mucus layer to contact the intestinal epithelial cells. The ability of nano drug delivery systems with neutral and hydrophilic surfaces to carry insulin through the mucus layer is an ideal feature of nanocarriers, but it may also weaken the interaction between the carrier and intestinal epithelial cells. Therefore, how to select suitable carrier materials, design and construct new nano drug delivery systems based on the physiological structure and transport and absorption characteristics of the intestinal mucosal epithelium, and achieve efficient oral delivery of insulin is a key issue that needs to be solved urgently.

[0007] There are many types of intestinal epithelial cells in the intestine, and there are abundant receptors on their surfaces. Based on these receptors, different types of intestinal targeted oral delivery systems can be developed to improve the absorption of drug delivery systems by intestinal epithelial cells. Common targeted receptors include: vitamins, neonatal Fc receptors, lectins and lectin mimetics, peptide ligands, goblet cell targeting receptors, M cell targeting receptors, dendritic cell targeting receptors, etc.

[0008] The small intestine can transport L-amino acids against the concentration gradient, mainly into enterocytes with the assistance of amino acid transporters, which are highly expressed in enterocytes. This property makes amino acids effective targeting ligands for enhancing drug delivery to the intestinal epithelium. L-Valine is an α-amino acid that is targeted to PepT1 by forming prodrugs or carriers using its dipeptides and esters. The antiviral drug NM283 (Valopicitabine) developed by Idenix in the UK is a valine ester of 2′-C-methylcytidine, which increases the bioavailability of the parent drug to 34% through PepT1-mediated transport. Ye et al. synthesized an antibody-drug conjugate by linking MC-Val-Cit-PBA-DOX to cetuximab, which was then adsorbed onto the surface of BSA nanoparticles, enabling targeted delivery of chemotherapeutic drugs to the site of diseased tissue.

[0009] Insulin administration is the primary strategy for treating type 1 and late-stage type 2 diabetes. However, due to the difficulty in controlling the insulin dose, the traditional direct insulin injection method is prone to hypoglycemia, which can lead to blindness, coma, epileptic seizures, renal failure, brain damage and even death. In recent years, the treatment system of glucose-responsive insulin release has shown more and more advantages. The system can simulate the dynamic physiological process of insulin secretion by pancreatic β cells, maintain blood sugar stability, and achieve precision medicine at the individual level. That is, the glucose-responsive component is integrated into the insulin delivery system to establish an "artificial pancreas" in the human circulatory system. It can sense the increase or decrease in blood sugar levels and respond to it, so that it can automatically and continuously control the amount of insulin released according to the blood sugar level. With the in-depth study of glucose-responsive drug carriers, self-regulating drug delivery systems have attracted widespread attention. At present, glucose-responsive self-regulating drug delivery systems mainly include glucose oxidase, concanavalin A (ConA), phenylboronic acid group and glucose binding protein, which can change their own properties or environmental characteristics according to the level of glucose concentration to regulate drug release.

[0010] The self-regulating insulin drug delivery system is particularly important for the treatment of insulin-dependent diabetes. When the blood sugar concentration is within the normal range, no insulin is released. When the blood sugar concentration is too high, insulin can be released in a controlled manner. The glucose-responsive system reflects the intelligence of the drug carrier and can significantly improve the quality of life of patients.

[0011] Phenylboronic acid and its derivatives can react reversibly with glucose, thereby regulating the release of insulin in composite nanoparticles. At present, glucose-responsive insulin delivery systems are mainly formed by coupling phenylboronic acid to natural polysaccharides (such as chitosan) or synthetic polymers, and then reacting with insulin to form glucose-responsive nanocarriers.

[0012] In summary, oral insulin faces multiple obstacles, especially the barrier of passing through the small intestinal epithelial cells, resulting in extremely low bioavailability. Traditional insulin-loaded delivery systems are also unable to maintain blood sugar homeostasis at the individual level and intelligently regulate insulin release. Summary of the invention

[0013] The present invention provides an insulin-loaded composite nanoparticle and a preparation method and application thereof, so as to solve the problems of low bioavailability of oral insulin and inability to intelligently regulate insulin release in the prior art.

[0014] In order to achieve the above object, the technical solution adopted by the present invention is:

[0015] An insulin-loaded composite nanoparticle has a core-shell structure, wherein the core is a polyelectrolyte complex formed by self-assembly of L-valine-modified chitosan and insulin, and the shell is an anionic polysaccharide selected from any one of fucoidan, carboxymethyl starch, gum arabic and pectin.

[0016] A method for preparing the above-mentioned composite nanoparticles loaded with insulin, the process is as follows:

[0017] preparing L-valine-modified chitosan, i.e., L-valine-chitosan, and preparing L-valine-chitosan into an L-valine-chitosan solution;

[0018] An insulin solution was prepared, and the insulin solution was slowly added dropwise to the L-valine-chitosan solution at a volume ratio of 1:1, and stirred at a stirring speed of 400-800 rpm for 10-30 min to obtain an L-valine-chitosan polyelectrolyte complex;

[0019] An anionic polysaccharide solution is prepared, wherein the anionic polysaccharide is selected from any one of fucoidan, carboxymethyl starch, gum arabic, and pectin; the L-valine-chitosan polyelectrolyte complex loaded with insulin is slowly added dropwise to the anionic polysaccharide solution, and then stirred at a stirring speed of 400-800 rpm for 20-40 min; then, the solution is centrifuged at a low speed of 4000 rpm for 15-30 min; finally, the supernatant is taken to obtain L-valine-chitosan-polysaccharide composite nanoparticles loaded with insulin, that is, composite nanoparticles loaded with insulin.

[0020] Further, the preparation process of L-valine-chitosan solution is as follows:

[0021] Add chitosan to the acetic acid aqueous solution, add 10 mg of chitosan to each ml of 1% acetic acid aqueous solution, then stir to completely dissolve, and then add an equal amount of PBS buffer to obtain a chitosan solution;

[0022] Boc-L-valine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and N-hydroxysuccinimide were sequentially added to DMSO in a molar ratio of 1:1.2:1.2, and reacted at 60°C for 4 hours to obtain NHS-(Boc-L-Val) ester;

[0023] Then, the chitosan solution was added to the NHS-(Boc-L-Val) ester, the pH was adjusted to 8-9, an appropriate amount of hydrochloric acid was added under ice bath, and the mixture was stirred at room temperature for 2 h to obtain a sample;

[0024] Next, the sample was placed in a dialysis bag and dialyzed in 10% ethanol water for 3 days. After the dialysis was completed, it was freeze-dried to obtain L-valine-modified chitosan, i.e., L-valine-chitosan;

[0025] Finally, add L-valine-chitosan to the 1% acetic acid aqueous solution, add 1 mg of L-valine-chitosan per milliliter of 1% acetic acid aqueous solution, stir overnight to dissolve, adjust the pH value of the solution to 3-6 with 1 mol / L NaOH, continue stirring for 5 hours, and obtain 1 mg / mL L-valine-chitosan solution.

[0026] Furthermore, when preparing the L-valine-chitosan polyelectrolyte complex, the pH of the L-valine-chitosan solution used is 4.5-5.5, and the pH of the insulin solution used is 7-8.

[0027] An application of the above-mentioned insulin-loaded composite nanoparticles for oral administration for the treatment of type I diabetes and type II diabetes.

[0028] A composite nanoparticle loaded with insulin has a multi-layer core-shell structure, wherein the core is a polyelectrolyte complex formed by self-assembly of gelatin modified with phenylboronic acid and insulin, and two shells are formed outside the polyelectrolyte complex by a layer-by-layer adsorption method, the first shell is chitosan modified with L-valine, and the second shell is fucoidan.

[0029] A method for preparing the above-mentioned composite nanoparticles loaded with insulin, the process is as follows:

[0030] preparing L-valine-modified chitosan, i.e., L-valine-chitosan, and preparing the L-valine-modified chitosan into an L-valine-modified chitosan solution, i.e., an L-valine-chitosan solution;

[0031] A phenylboronic acid-modified gelatin solution is prepared, and an insulin solution is prepared; the phenylboronic acid-modified gelatin solution is added dropwise to the insulin solution, and stirred at a stirring speed of 400-800 rpm for 20-40 min to obtain a polyelectrolyte complex formed by the phenylboronic acid-modified gelatin and insulin;

[0032] The polyelectrolyte complex formed by phenylboronic acid-modified gelatin and insulin is mixed with an equal volume of 1 mg / mL L-valine-chitosan solution, and stirred at a stirring speed of 400-800 rpm for 10-30 min to obtain a nanoparticle complex;

[0033] An equal volume of a fucoidan solution with a concentration of 2 mg / mL is added to the nanocomplex, stirred at a stirring speed of 400-800 rpm for 10-30 min, and then centrifuged at a centrifugal speed of 4000 rpm for 15-30 min; finally, the supernatant is taken to obtain composite nanoparticles with a multilayer core-shell structure double-modified with phenylboronic acid and L-valine loaded with insulin, that is, composite nanoparticles loaded with insulin.

[0034] Further, the preparation process of the phenylboronic acid modified gelatin solution is as follows:

[0035] Pure water and DMSO were mixed in a volume ratio of 1:4 to form a mixed solvent, gelatin was added to the mixed solvent, 40 mg of gelatin was added to each milliliter of the mixed solvent, the pH was adjusted to 5 with HCl, and then heated to dissolve;

[0036] Then, amino-substituted phenylboronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and N-hydroxysuccinimide were dissolved in a mixed solution of pure water and DMSO at a molar ratio of 7:1.2:1.2, wherein the volume ratio of pure water to DMSO in the mixed solution was 1:4, and the pH was adjusted to 5 with HCl;

[0037] The mixed solution containing gelatin is mixed with a mixed solution containing amino-substituted phenylboronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, stirred at room temperature for 48 hours, and then placed in a dialysis bag for dialyzing for one week. After the dialysis is completed, the mixture is freeze-dried to obtain phenylboronic acid-modified gelatin;

[0038] The phenylboronic acid-modified gelatin was dissolved in deionized water to prepare a phenylboronic acid-modified gelatin solution with a concentration of 1 mg / mL, and the pH was adjusted to 4.

[0039] Furthermore, the amino-substituted phenylboronic acid is any one of 4-aminophenylboronic acid, 3-aminophenylboronic acid, 3-fluoro-4-aminophenylboronic acid, and 3-nitro-4-aminophenylboronic acid.

[0040] The above-mentioned composite nanoparticles loaded with insulin are used for oral administration and injection for the treatment of diabetes.

[0041] The invention provides a composite nanoparticle loaded with insulin, wherein the core is a polyelectrolyte complex formed by self-assembly of chitosan modified with L-valine and insulin, and the shell is an anionic polysaccharide. The invention modifies chitosan with L-valine to improve its targeting and uptake capacity of intestinal epithelial cells. Then, under appropriate conditions, it reacts with insulin to form a nanoscale polyelectrolyte complex (PEC). However, this nanoparticle is easily destroyed under gastric acid conditions due to its solubility in an acidic environment, so the invention further modifies the surface of the polyelectrolyte complex with anionic polysaccharides, such as fucoidan, to form core-shell nanoparticles.

[0042] The present invention also provides a composite nanoparticle loaded with insulin having a multi-layer core-shell structure, wherein the core is a polyelectrolyte complex formed by self-assembly of gelatin modified with phenylboronic acid and insulin, and two shells are formed outside the polyelectrolyte complex by a layer-by-layer adsorption method: chitosan modified with L-valine and a shell of fucoidan. The present invention designs a novel multi-layer core-shell structure with glucose responsiveness by a layer-by-layer adsorption method. Gelatin is a hydrophilic biomacromolecule with high safety, high biocompatibility, low cost and easy availability, which contains abundant amino and carboxyl groups, is easy to modify, and can be coupled with the responsive molecule phenylboronic acid. The gelatin grafted with phenylboronic acid is used to react with insulin to form the core; the chitosan modified with L-valine is used to form the first layer of the core-shell structure, and the outer layer is adsorbed on the surface of fucoidan to form a double-modified glucose-responsive multi-layer core-shell structure nanoparticle.

[0043] In the composite nanoparticles loaded with insulin of the multi-layer core-shell structure of the present invention, the gelatin grafted with phenylboronic acid is placed in the innermost layer (i.e., the inner core) so that it is not affected in the gastrointestinal tract, and can enter the blood circulation to the maximum extent after the nanocarrier passes through the gastrointestinal tract to play a role, and play the role of glucose response and blood sugar regulation; and the outer layer is a layer of chitosan modified with L-valine, which can play its targeting role in intestinal epithelial cells and improve the ability to pass through intestinal epithelial cells and enter the blood circulation; and the outermost layer is a fucoidan layer, which has a large negative charge density and can form a zeta potential with a high absolute value, which is conducive to the stability of the nanoparticles, and a certain amount of surface negative charge is conducive to passing through the mucus layer between the intestinal contents and the epithelial cells, which is conducive to the nanoparticles reaching the epithelial cells. Such a three-layer structure can not only effectively protect insulin from gastrointestinal damage, but also facilitate step-by-step passing through the mucus layer, passing through the epithelial cells, and realizing glucose response in the blood.

[0044] Compared with the prior art, the present invention has the following advantages:

[0045] 1. When designing the insulin delivery system, the present invention grafts a certain amount of L-valine on chitosan, which can target intestinal epithelial cells and improve the penetration rate of epithelial cells. Through oral experiments on diabetic mice, it is proved that it can effectively reduce the blood sugar of mice, and the blood sugar-lowering effect can last for a long time, avoiding excessive fluctuations in blood sugar concentration;

[0046] 2. The present invention also designs an L-valine and phenylboronic acid dual-modified insulin nano drug delivery system based on gelatin, chitosan and fucoidan, which has intestinal targeting and glucose responsiveness, and can adjust the amount of insulin release according to blood sugar levels, reflecting the intelligence of the drug delivery system. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The synthetic route and characterization diagram of L-valine-chitosan in Example 1 of the present invention, wherein: (A) is the synthetic route of L-valine-chitosan (VCS); (B) is the infrared spectra of chitosan (CS) and L-valine-chitosan (VCS); (C) is the nuclear magnetic hydrogen spectra of L-valine, chitosan (CS) and L-valine-chitosan (VCS).

[0048] Figure 2 This is a transmission electron microscope image of the sample prepared in Example 2 of the present invention.

[0049] Figure 3 : is the enzyme stability and storage stability diagram in the embodiment of the present invention, wherein: (A) is the degradation curve of free insulin, INS-PEC and INS-NPs in pepsin; (B) is the degradation curve of free insulin (Free insulin), INS-PEC and INS-NPs in trypsin. * indicates that it is significant compared with the free insulin group (p<0.05); (C) is the storage stability of INS-NPs, and different letters in the figure indicate significant differences (p<0.05).

[0050] Figure 4 It is the in vitro release curve of insulin in the embodiment of the present invention.

[0051] Figure 5 The laser confocal scanning microscope images of Caco-2 cells treated with different nanoparticles loaded with FITC-insulin in the embodiments of the present invention, left: CS-INS-FUNPs based on unmodified chitosan; right: VCS-INS-FU NPs based on L-valine modified chitosan). The blue signal represents the cell nucleus stained with DAPI, and the green signal represents FITC-labeled insulin. The scale bar is 20 μm.

[0052] Figure 6This is the relationship between the change rate of blood glucose level of diabetic mice with time in different administration methods in the embodiments of the present invention. DETAILED DESCRIPTION

[0053] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0054] Example 1 Synthesis of L-valine modified chitosan (L-valine-chitosan, abbreviated as VCS)

[0055] The synthetic route of L-valine modified chitosan is as follows Figure 1 As shown in A, the specific steps are as follows:

[0056] ① 100 mg chitosan (CS) was dissolved in 10 mL 1% acetic acid aqueous solution, stirred until completely dissolved, and then an equal amount of PBS buffer was added to prepare a chitosan solution;

[0057] ② Add Boc-L-valine, 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) to DMSO in a molar ratio of 1:1.2:1.2, stir to dissolve, and react at 60°C for 4 hours to obtain NHS-(Boc-L-Val) ester; the molar ratio of Boc-L-valine to chitosan is 2:1, and when calculating the molar number, the molecular weight of chitosan is calculated as a monomer;

[0058] ③ Add the chitosan solution prepared in ① to the NHS-(Boc-L-Val) ester prepared in ②, adjust the pH of the system to 8-9 with triethylamine, add an appropriate amount of hydrochloric acid under ice bath, and stir at room temperature for 2h;

[0059] ④ The sample obtained in ③ is placed in a dialysis bag and dialyzed in 10% ethanol water for 3 days. After the dialysis is completed, it is freeze-dried to obtain L-valine modified chitosan, namely L-valine-chitosan (VCS).

[0060] Fourier transform infrared spectroscopy and nuclear magnetic resonance hydrogen spectrum were used to characterize L-valine-chitosan. Figure 1 B and Figure 1 C. FTIR: 3357.47cm - 1 (OH stretching vibration peak), 2882.11 (CH stretching vibration), 1630.45 cm - 1 (amide I band, C=O stretching vibration), 1525.96 cm - 1 (amide II band, CN stretching vibration and NH bending vibration). 1HNMR (600 MHz, D2O / TFA 10:1) δ 0.72 ppm (two terminal methyl protons of grafted L-valine), 2.9-4 ppm (protons of chitosan units), 1.8 ppm (-COCH3 in the chitosan skeleton).

[0061] The grafting degree was calculated based on the integrated area of ​​the peak corresponding to the two terminal methyl protons of grafted L-valine and the integrated area of ​​the peak corresponding to the protons of the chitosan unit in the nuclear magnetic resonance spectrum. The grafting degree of L-valine was 12%.

[0062] Example 2 Preparation of insulin (INS) loaded composite nanoparticles based on L-valine-chitosan (VCS for short) and fucoidan (FU for short), the process is as follows:

[0063] (1) Preparation of L-valine-chitosan solution

[0064] Weigh 5 mg of L-valine-chitosan prepared in Example 1 and dissolve it in 5 mL of 1% acetic acid aqueous solution, stir and dissolve overnight, adjust the pH value of the solution to 5.2 with 1 mol / L NaOH, and continue stirring for 5 h to obtain 5 mL of 1 mg / mL L-valine-chitosan solution;

[0065] (2) Preparation of insulin solution

[0066] Dissolve 5 mg of insulin in 5 mL of a mixed solution of 0.01 mol / L HCl and 0.1 mol / L Tris, stir thoroughly to dissolve, and adjust the pH to 7.8 to obtain 5 mL of a 1 mg / mL insulin solution;

[0067] (3) Preparation of insulin-loaded L-valine-chitosan polyelectrolyte complex (PEC) (abbreviated as INS-PEC)

[0068] Slowly add 5 mL of the insulin solution obtained in step (2) to 5 mL of the L-valine-chitosan solution obtained in step (1) at a stirring speed of 500 rpm for 20 min;

[0069] (4) Preparation of fucoidan solution

[0070] Dissolve 10 mg of fucoidan in 20 mL of deionized water and stir overnight to obtain a fucoidan solution;

[0071] (5) Preparation of insulin-loaded L-valine-chitosan-fucoidan composite nanoparticles

[0072] The insulin-loaded L-valine-chitosan polyelectrolyte complex obtained in (3) was slowly added dropwise to the fucoidan solution obtained in (4), with stirring at a speed of 500 rpm for 30 min, and then centrifuged at a low speed of 4000 rpm for 20 min, and the supernatant was collected to obtain insulin-loaded L-valine-chitosan-fucoidan composite nanoparticles (abbreviated as VCS-INS-FU NPs or INS-NPs).

[0073] Example 3 The particle size, potential, insulin encapsulation efficiency and drug loading of the sample prepared in Example 2 were measured as follows:

[0074] (1) The particle size and potential of the nanoparticles were detected using a Malvern dynamic light scattering instrument from the UK. The average particle size was 198 nm, the PDI was 0.18, and the zeta potential was -33 mV.

[0075] (2) Use transmission electron microscopy to characterize the morphology of nanoparticles. Drop the diluted nanoparticle dispersion onto the coated copper mesh. After 5 to 10 minutes, use filter paper to absorb the excess liquid from the side and dry it naturally. Use a transmission electron microscope (JEM-1400Flash, Japan) at an accelerating voltage of 120 kV to observe and photograph the morphology of the sample. See the attached Figure 2 .

[0076] (3) Determination of insulin encapsulation efficiency

[0077] The freshly prepared nanoparticle solution was centrifuged at 12000 rpm for 40 min, and the supernatant was filtered with a 0.22 μm filter membrane. The corresponding peak area was measured at 214 nm and retention time 9.6 min using a high performance liquid chromatography (HPLC). The standard curve was y = 16.479x - 15.655 (R 2 =0.9998) to calculate the content of insulin, and the insulin encapsulation efficiency is calculated as follows:

[0078] Encapsulation efficiency = (total insulin amount - free insulin amount) / total insulin amount × 100%

[0079] Drug loading = (total insulin amount - free insulin amount) / total mass of nanoparticles × 100%

[0080] After testing, the encapsulation efficiency of insulin in the sample prepared in Example 2 was 91.2%, and the drug loading was 12.3%. Example 4 Preparation and characterization of L-valine-chitosan-carboxymethyl starch composite nanoparticles (abbreviated as VCS-INS-CMS NPs), the process is as follows:

[0081] (1) Preparation of L-valine-chitosan solution

[0082] 5 mg of L-valine-chitosan prepared in Example 1 was dissolved in 5 mL of 1% acetic acid aqueous solution, stirred overnight to dissolve, the pH value of the solution was adjusted to 5.2 with 1 mol / L NaOH, and stirring was continued for 5 h to obtain 5 mL of 1 mg / mL L-valine-chitosan solution;

[0083] (2) Preparation of insulin solution

[0084] Dissolve 5 mg of insulin in 5 mL of a mixed solution of 0.01 mol / L HCl and 0.1 mol / L Tris, stir thoroughly to dissolve, and adjust the pH to 7.8 to obtain 5 mL of a 1 mg / mL insulin solution;

[0085] (3) Preparation of insulin-loaded L-valine-chitosan polyelectrolyte complex (PEC) (abbreviated as INS-PEC)

[0086] Slowly add 5 mL of the insulin solution obtained in step (2) to 5 mL of the L-valine-chitosan solution obtained in step (1) at a stirring speed of 500 rpm for 20 min;

[0087] (4) Preparation of carboxymethyl starch solution

[0088] Dissolve 10 mg of carboxymethyl starch in 20 mL of deionized water and stir to dissolve to obtain a carboxymethyl starch solution;

[0089] (5) Preparation of insulin-loaded L-valine-chitosan-carboxymethyl starch composite nanoparticles

[0090] The insulin-loaded L-valine-chitosan polyelectrolyte complex obtained in (3) was slowly added dropwise to the carboxymethyl starch solution obtained in (4), with stirring at a speed of 500 rpm for 30 min, and then centrifuged at a low speed of 4000 rpm for 20 min, and the supernatant was collected to obtain insulin-loaded L-valine-chitosan-carboxymethyl starch composite nanoparticles (abbreviated as VCS-INS-CMS NPs).

[0091] According to the detection method of Example 3, the average particle size of the insulin-loaded L-valine-chitosan-carboxymethyl starch composite nanoparticles was 216 nm, the PDI was 0.21, the zeta potential was -31 mV, the insulin encapsulation efficiency was 90.6%, and the drug loading was 11.8%.

[0092] Example 5 Stability Study

[0093] The samples prepared in Example 2 were subjected to stability tests against enzyme degradation in different enzyme solutions, including the insulin-loaded L-valine-chitosan polyelectrolyte complex (INS-PEC) prepared in step (3), the insulin-loaded L-valine-chitosan-fucoidan composite nanoparticles (INS-NPs) prepared in step (5), and free insulin.

[0094] Enzyme solutions included pepsin solution (pH 2.0, 125 IU mL -1 ) and trypsin solution (pH 6.8, 250 IU·mL -1 ).

[0095] For the anti-pepsin experiment, 600 μL of freshly prepared insulin-loaded nanoparticle samples were added to an equal volume of pepsin solution and incubated in a shaker at 37°C and 80 rpm for 2 h. For the anti-trypsin experiment, 600 μL of freshly prepared insulin-loaded nanoparticle samples were added to an equal volume of trypsin solution and incubated in a shaker at 37°C and 80 rpm for 6 h. Then, 0.3 mL of cold NaOH solution (0.01 M) was added to stop the pepsin activity, or 0.3 mL of cold HCl solution (0.1 M) was added to stop the trypsin activity. The samples were then ultrasonically treated to destroy the nanoparticles and release insulin. Finally, the amount of remaining insulin was determined by HPLC.

[0096] The results are as follows Figure 3 As shown in A and 3B, Figure 3 A is the result of anti-pepsin test. Figure 3 B is the result of the anti-trypsin experiment, which shows that the insulin-loaded L-valine-chitosan-fucoidan nanoparticle complex (INS-NPs) can significantly improve the enzyme resistance of insulin, while the insulin-loaded L-valine-chitosan polyelectrolyte complex (INS-PEC) has a lower anti-enzyme activity, and the stability of both against enzyme degradation is much higher than that of free insulin.

[0097] The L-valine-chitosan-fucoidan composite nanoparticles (INS-NPs) prepared in Example 2 were stored in a refrigerator at 4°C, and the particle size was analyzed at different time intervals (3, 7, 14, 21 and 28 days) to study its storage stability. Figure 3 As shown in C, it shows that the L-valine-chitosan-fucoidan nanoparticle complex loaded with insulin has excellent storage stability.

[0098] Example 6 In vitro simulated gastrointestinal sustained release experiment

[0099] For the insulin-loaded L-valine-chitosan polyelectrolyte complex (INS-PEC) prepared in step (3) of Example 2, the insulin-loaded L-valine-chitosan-fucoidan nanoparticle complex (INS-NPs) prepared in step (5) and the free insulin solution (Free-insulin), the insulin release behavior was studied in enzyme-free simulated gastric fluid (SGF, pH = 2.0) and enzyme-free simulated intestinal fluid (SIF, pH = 6.8).

[0100] The insulin-loaded L-valine-chitosan polyelectrolyte complex (INS-PEC) in step (3) of Example 2, the insulin-loaded L-valine-chitosan-fucoidan nanoparticle complex (INS-NPs) in step (5), and the free insulin solution (Free-insulin) were added to a dialysis bag (MWCO 8000-14000Da) respectively. The dialysis bag was then suspended in a conical flask filled with SGF, and the conical flask was incubated at 37°C and 100 rpm for 2 hours; thereafter, the dialysis bag was placed in a conical flask filled with SIF and continued to be incubated at 37°C and 100 rpm for 10 hours. During this process, 1 mL of the mixture was taken out at certain time intervals and supplemented with the same amount of fresh SGF or SIF. Finally, the sample was centrifuged at high speed (14000rpm / min) for 30 minutes, and the amount of released insulin was measured by HPLC.

[0101] Figure 4 The release curves of the three samples in an enzyme-free environment simulated the gastrointestinal environment, and the results showed that about 90% of the free insulin was released within 1 hour. In contrast, the insulin encapsulated in INS-PEC released about 40% within 2 hours of SGF, and then gradually released in the subsequent SIF stage, with a cumulative release rate of about 60% after 12 hours of incubation. For INS-NPs nanoparticles, only 20% of insulin was released in the initial 2 hours of SGF, which was significantly lower than the amount observed in INS-PEC. The fucoidan coating effectively prevented the structural expansion of the L-valine-chitosan polyelectrolyte complex in SGF, thereby reducing insulin leakage. In the subsequent SIF stage, the release curve was similar to that of INS-PEC, and the cumulative release rate was less than 50% after 12 hours of incubation. It shows that the core-shell structured nanoparticles coated with fucoidan have obvious drug sustained release effect.

[0102] Example 7 Cellular uptake experiment

[0103] Insulin was labeled with FITC (fluorescein isothiocyanate-labeled insulin) and nanoparticles were prepared using FITC-labeled insulin. The ability of the insulin-loaded nanoparticles to enter cells was analyzed using a laser confocal scanning microscope on Caco-2 cells.

[0104] Preparation of FITC-labeled insulin (FITC-INS): Refer to International Journal of Biological Macromolecules 276 (2024) 133805. The specific steps are as follows: dissolve FITC in DMSO at a concentration of 1 mg / mL, dissolve insulin in a 0.1M Na2CO3 solution at a concentration of 4 mg / mL, and mix with FITC solution at a volume ratio of 1:3. The mixture was stirred at 4°C in the dark for 24 hours. Subsequently, an appropriate amount of 50mM NH4Cl solution was added and stirred at room temperature for 2 hours to terminate the reaction. Finally, dialyzed (MWCO 3500Da) with phosphate buffer (pH = 7.2) for 3 days and then lyophilized.

[0105] Nanoparticles were prepared using FITC-labeled insulin, and the specific method was consistent with the method in Example 2, except that the insulin was replaced with FITC-labeled insulin. Including insulin-loaded nanoparticles (FITC-INS / VCS-FUNPs) formed by chitosan and fucoidan modified with L-valine, and insulin-loaded nanoparticles (FITC-INS / CS-FUNPs) formed by chitosan and fucoidan without L-valine modification. By comparing the cell uptake capacity of the two, the advantage of L-valine modification was determined.

[0106] Caco-2 cells were cultured in 24-well plates and incubated for 24 hours. The cells were then treated with fresh medium containing FITC-INS / CS-FU NPs and FITC-INS / VCS-FU NPs (50 μg / mL) for 1 hour, 3 hours, and 6 hours, respectively. After the incubation, the cell monolayer was rinsed three times with cold PBS solution, fixed with 4% cold paraformaldehyde at 37°C for 30 minutes, and then stained with DAPI solution for 15 minutes to mark the cell nucleus. Finally, the cells were imaged using a laser confocal scanning microscope.

[0107] Figure 5The cell uptake diagrams of FITC-INS / CS-FU NPs (left) and FITC-INS / VCS-FUNPs (right). The cell nucleus stained with DAPI emits blue fluorescence, while FITC-bound insulin emits green fluorescence. The increase in green fluorescence intensity indicates an increase in the cell uptake of nanoparticles. Laser confocal scanning microscopy showed that after incubation for 1 hour, 3 hours, and 6 hours, the green fluorescence intensity in cells treated with L-valine-modified nanoparticles (VCS-INS-FU NPs) was greater than that of nanoparticles not modified with L-valine (CS-INS-FU NPs), indicating that L-valine modification can improve the ability of insulin to pass through the cell membrane and enter the cell, and the VCS-FU nanoparticle carrier loaded with insulin exhibits better cellular internalization ability.

[0108] Example 8 Animal hypoglycemic experiment

[0109] The L-valine-chitosan-fucoidan composite nanoparticles (VCS-INS-FUNPs) prepared in Example 2 were orally administered to investigate their hypoglycemic effect in diabetic model mice.

[0110] ICR mice (4-5 weeks, 18-22g) were induced to diabetes by subcutaneous injection of 150mg / kg dose of streptozotocin (STZ). The mice were divided into six groups, 10 in each group: a positive control group (subcutaneous injection of insulin, 5IU / kg), a negative control group (oral insulin solution, 50IU / kg), a blank control group (oral 0.9% saline), and a high, medium and low dose drug group, i.e., the L-valine-chitosan-fucoidan composite nanoparticles (VCS-INS-FU NPs) prepared in Example 2 were orally administered at insulin doses of 30, 50 and 100IU / kg, respectively, and blood glucose levels were monitored using a blood glucose meter. The relative pharmacological bioavailability (relative PA, %) was calculated by the following formula:

[0111]

[0112] AAC oral It refers to the difference in the area under the blood glucose curve between the oral administration group and the blank control group, AAC sc It refers to the difference in the area under the blood glucose curve between the subcutaneous injection group and the blank control group. sc Dose refers to the dose of insulin injected subcutaneously. oral Refers to the insulin dose of the oral administration group.

[0113] Figure 6Figure 2 is the blood glucose lowering curve of the prepared nanoparticles on fasting T1DM model mice. Figure 6 As shown in the figure, after subcutaneous injection of insulin solution (5IU / kg), blood glucose levels dropped sharply within 2 hours, but returned to baseline levels within 8 hours. This means that subcutaneous injection of insulin causes significant fluctuations in blood glucose levels and is only effective in lowering blood glucose for a short period of time. Oral administration of normal saline and oral insulin solution had no significant effect on blood glucose levels. The hypoglycemic effects of different doses of insulin-loaded nanoparticles showed that VCS-INS-FU NPs showed good hypoglycemic effects after oral administration, and the hypoglycemic effect was correlated with the insulin dose. At doses of 30IU / kg and 50IU / kg, blood glucose levels reached their lowest point after 8 hours and then rose slightly. In contrast, the 100IU / kg dose showed a significant hypoglycemic effect within 12 hours, and the duration of sustained hypoglycemia was longer.

[0114] By calculating the relative pharmacological bioavailability of VCS-INS-FU NPs, within 12 hours, when the insulin dose was 30IU / kg, the relative pharmacological bioavailability was the highest, reaching 10.93%. When the oral dose was 50IU / kg, the relative bioavailability was 8.53%. Therefore, oral VCS-INS-FU NPs showed significant hypoglycemic effects and high relative pharmacological bioavailability, and blood sugar dropped more steadily and could last for a longer period of time.

[0115] Example 9 Animal hypoglycemic experiment

[0116] The L-valine-chitosan-carboxymethyl starch composite nanoparticles (VCS-INS-CMSNPs) prepared in Example 4 were orally administered to investigate their hypoglycemic effect in diabetic model mice.

[0117] ICR mice (4-5 weeks, 18-22g) were induced to diabetes by subcutaneous injection of 150mg / kg dose of streptozotocin (STZ). The mice were divided into six groups, 10 in each group: a positive control group (subcutaneous injection of insulin, 5IU / kg), a negative control group (oral insulin solution, 50IU / kg), a blank control group (oral 0.9% saline), a high, medium and low dose drug group, i.e., the L-valine-chitosan-carboxymethyl starch composite nanoparticles (VCS-INS-CMS NPs) prepared in Example 4 were orally administered at insulin doses of 30, 50 and 100IU / kg, and blood glucose levels were monitored using a blood glucose meter. The relative pharmacological bioavailability (relative PA, %) was calculated by the following formula:

[0118]

[0119] AAC oral It refers to the difference in the area under the blood glucose curve between the oral administration group and the blank control group, AAC sc It refers to the difference in the area under the blood glucose curve between the subcutaneous injection group and the blank control group. sc Dose refers to the dose of insulin injected subcutaneously. oral Refers to the insulin dose of the oral administration group.

[0120] Table 1 Hypoglycemic activity of oral L-valine-chitosan-carboxymethyl starch composite nanoparticles prepared in Example 4 on fasting T1DM model mice

[0121]

[0122]

[0123] As can be seen from Table 1, oral insulin solution has basically no effect on blood sugar, and the L-valine-chitosan-carboxymethyl starch composite nanoparticles (VCS-INS-CMS NPs) prepared by oral Example 4 all show good hypoglycemic effects, and the hypoglycemic effect is also correlated with the insulin dose. At the doses of 30IU / kg and 50IU / kg, blood sugar levels reached the lowest point after 8 hours, and then rose slightly. In contrast, the 100IU / kg dose showed a better hypoglycemic effect and lasted longer.

[0124] Example 10 Preparation process of composite nanoparticles double modified by phenylboronic acid and L-valine:

[0125] (1) Preparation of phenylboronic acid modified gelatin (refer to the literature, slightly modified A novel injectable hydrogel prepared from phenylboronic acid modiffed gelatin and oxidized-dextran for bone tissue engineering, International Journal of Biological Macromolecules 261(2024)129666)

[0126] Weigh 2 g of gelatin and add it to 50 mL of a mixed solution of pure water and DMSO (volume ratio 1:4), adjust the pH to 5 with 0.1 M HCl, and heat to dissolve;

[0127] 3-Aminophenylboronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) were dissolved in 50 mL of a mixed solution of pure water and DMSO (volume ratio 1:4) in a molar ratio of 7:1.2:1.2, and the pH was adjusted to 5 with 0.1 M HCl;

[0128] The two liquids were mixed, stirred at room temperature for 48 hours, placed in a dialysis bag and dialyzed for one week. After the dialysis was completed, the sample was freeze-dried to obtain phenylboronic acid-modified gelatin.

[0129] (2) Preparation of phenylboronic acid modified gelatin solution

[0130] Dissolve 5 mg of phenylboronic acid-modified gelatin in 5 mL of deionized water and adjust the pH to 4 to obtain a phenylboronic acid-modified gelatin solution;

[0131] (3) Preparation of insulin solution

[0132] Dissolve 20 mg of insulin in 10 mL of a mixed solution of 0.01 mol / L HCl and 0.1 mol / L Tris, stir thoroughly to dissolve, and adjust the pH to 7.7 to obtain 10 mL of a 2 mg / mL insulin solution;

[0133] (4) Preparation of phenylboronic acid-modified gelatin and insulin polyelectrolyte complex

[0134] 5 mL of the phenylboronic acid-modified gelatin solution obtained in step (2) was added dropwise to 10 mL of the insulin solution prepared in step (3), with stirring at a speed of 600 rpm for 30 min, to obtain a polyelectrolyte complex formed by phenylboronic acid-modified gelatin and insulin;

[0135] (5) The polyelectrolyte complex formed by the phenylboronic acid-modified gelatin and insulin obtained in step (4) was mixed with 15 mL of a 1 mg / mL L-valine-modified chitosan solution, and stirred at a speed of 500 rpm for 20 min. The preparation method of the 1 mg / mL L-valine-modified chitosan solution is as described in step (1) of Example 2.

[0136] (6) Take the nanoparticle complex obtained in step (5), add 30 mL of 2 mg / mL fucoidan solution, stir at 600 rpm for 25 min; then centrifuge at 4000 rpm for 20 min, and take the supernatant to obtain insulin-loaded composite nanoparticles with a multilayer core-shell structure double-modified with phenylboronic acid and L-valine.

[0137] The analysis showed that the average particle size of the nanoparticles was 203 nm, the PDI was 0.14, the zeta potential was -39 mV, the insulin encapsulation efficiency was 95.5%, and the drug loading was 18.6%.

[0138] Example 11 In vitro glucose responsiveness study of the composite nanoparticles double-modified with phenylboronic acid and L-valine prepared in Example 10

[0139] Glucose responsiveness is mainly evaluated by the change in the size of nanoparticles over time in different concentrations of glucose medium. Different nanoparticles were dispersed in PBS solution, and different concentrations of glucose solution (0, 1, 2, 3 mg / mL) were added and mixed thoroughly. At different time intervals, the change in the particle size of the nanoparticles was measured by dynamic light scattering. Each group of experiments was measured three times in parallel to evaluate the glucose responsiveness of the nanoparticles.

[0140] The same method was used to measure the change in the particle size of the composite nanoparticles that were not modified with phenylboronic acid (i.e., the composite nanoparticles modified with L-valine, i.e., the insulin-loaded L-valine-chitosan-fucoidan composite nanoparticles of Example 2) for comparison.

[0141] Table 2 Effect of different nanoparticle sizes on glucose concentration

[0142]

[0143]

[0144] As shown in Table 2, the particle size of the composite nanoparticles modified with phenylboronic acid and L-valine becomes larger in the glucose solution, and the higher the glucose concentration, the greater the increase in particle size. In contrast, the particle size of the composite nanoparticles modified with L-valine changes very little, and only increases slightly even at high concentrations. This indicates that the composite nanoparticles modified with phenylboronic acid and L-valine have good glucose responsiveness.

[0145] Example 12 Insulin release rate of composite nanoparticles at different glucose concentrations

[0146] For the composite nanoparticles double-modified with phenylboronic acid and L-valine prepared in Example 10, the change of insulin release with glucose concentration was studied.

[0147] The composite nanoparticles were placed in dialysis bags and placed in PBS buffers with different glucose contents. 1 mL of release solution was taken at predetermined times (1, 2, 4, 8, 12, and 24 h), and the same volume of PBS was added to determine the cumulative release of insulin.

[0148] The same method was used to measure the insulin release rate of composite nanoparticles that were not modified with phenylboronic acid (i.e., composite nanoparticles modified with L-valine, i.e., the insulin-loaded L-valine-chitosan-fucoidan composite nanoparticles of Example 2) for comparison.

[0149] Table 3 Effect of different nanoparticles on insulin release rate as a function of glucose concentration

[0150]

[0151]

[0152] As shown in Table 3, the 12h insulin release rate of the composite nanoparticles double modified by phenylboronic acid and L-valine is 52.5% when the glucose concentration is low (1 mg / mL), which is higher than the insulin release rate of the composite nanoparticles modified by L-valine (44.5%); the 12h insulin release rate of the double-modified composite nanoparticles is 70.6% when the glucose concentration is 2 mg / mL, which is significantly higher than the insulin release rate of the composite nanoparticles modified by L-valine (41.4%); when the glucose concentration is higher (3 mg / mL), the 12h insulin release rate of the double-modified composite nanoparticles is 77.1%, which is much higher than the insulin release rate of the composite nanoparticles modified by L-valine (43.9%). This shows that the double-modified composite nanoparticles loaded with insulin have good glucose responsiveness.

[0153] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. The embodiments described in the present invention are merely descriptions of the preferred embodiments of the present invention, and do not limit the concept and scope of the present invention. The various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction, and such combinations should also be regarded as the contents disclosed in the present disclosure as long as they do not violate the concept of the present invention. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0154] The present invention is not limited to the specific details of the above-mentioned embodiments. Within the technical concept of the present invention and without departing from the design concept of the present invention, various modifications and improvements made to the technical solution of the present invention by technical personnel in this field should fall within the protection scope of the present invention. The technical contents for which protection is sought in the present invention have been fully recorded in the claims.

Claims

1. A composite nanoparticle loaded with insulin, characterized in that: It has a core-shell structure, wherein the core is a polyelectrolyte complex formed by self-assembly of chitosan modified by L-valine and insulin, and the shell is an anionic polysaccharide selected from any one of fucoidan, carboxymethyl starch, gum arabic and pectin.

2. A method for preparing insulin-loaded composite nanoparticles as claimed in claim 1, characterized in that: The process is as follows: preparing L-valine-modified chitosan, i.e., L-valine-chitosan, and preparing the L-valine-chitosan into an L-valine-chitosan solution; An insulin solution was prepared, and the insulin solution was slowly added dropwise to the L-valine-chitosan solution at a volume ratio of 1:1, and stirred at a stirring speed of 400-800 rpm for 10-30 min to obtain an L-valine-chitosan polyelectrolyte complex; An anionic polysaccharide solution is prepared, wherein the anionic polysaccharide is selected from any one of fucoidan, carboxymethyl starch, gum arabic, and pectin; the L-valine-chitosan polyelectrolyte complex loaded with insulin is slowly added dropwise to the anionic polysaccharide solution, and then stirred at a stirring speed of 400-800 rpm for 20-40 min; then, the solution is centrifuged at a low speed of 4000 rpm for 15-30 min; finally, the supernatant is taken to obtain L-valine-chitosan-polysaccharide composite nanoparticles loaded with insulin, that is, composite nanoparticles loaded with insulin.

3. The method for preparing insulin-loaded composite nanoparticles according to claim 2, characterized in that: The preparation process of L-valine-chitosan solution is as follows: Add chitosan to the acetic acid aqueous solution, add 10 mg of chitosan to each ml of 1% acetic acid aqueous solution, then stir to completely dissolve, and then add an equal amount of PBS buffer to obtain a chitosan solution; Boc-L-valine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and N-hydroxysuccinimide were sequentially added to DMSO at a molar ratio of 1:1.2:1.2, and reacted at 60°C for 4 hours to obtain NHS-(Boc-L-Val) ester; Then, the chitosan solution was added to the NHS-(Boc-L-Val) ester, the pH was adjusted to 8-9, an appropriate amount of hydrochloric acid was added under ice bath, and the mixture was stirred at room temperature for 2 h to obtain a sample; Next, the sample was placed in a dialysis bag and dialyzed in 10% ethanol water for 3 days. After the dialysis was completed, it was freeze-dried to obtain L-valine-modified chitosan, i.e., L-valine-chitosan. Finally, add L-valine-chitosan to the 1% acetic acid aqueous solution. Add 1 mg of L-valine-chitosan per milliliter of 1% acetic acid aqueous solution, stir overnight to dissolve, adjust the pH value of the solution to 3-6 with 1 mol / L NaOH, and continue stirring for 5 hours to obtain 1 mg / mL L-valine-chitosan solution.

4. The method for preparing insulin-loaded composite nanoparticles according to claim 2, characterized in that: When preparing L-valine-chitosan polyelectrolyte complex, the pH of L-valine-chitosan solution used is 4.5-5.5, and the pH of insulin solution used is 7-8.

5. Use of the insulin-loaded composite nanoparticles as claimed in claim 1 for oral administration for the treatment of type I diabetes and type II diabetes.

6. A composite nanoparticle loaded with insulin, characterized in that: It has a multi-layer core-shell structure, in which the inner core is a polyelectrolyte complex formed by self-assembly of gelatin modified with phenylboronic acid and insulin, and then two shells are formed outside the polyelectrolyte complex by a layer-by-layer adsorption method. The first shell is chitosan modified with L-valine, and the second shell is fucoidan.

7. A method for preparing insulin-loaded composite nanoparticles as claimed in claim 6, characterized in that: The process is as follows: preparing L-valine-modified chitosan, i.e., L-valine-chitosan, and preparing the L-valine-modified chitosan into an L-valine-modified chitosan solution, i.e., an L-valine-chitosan solution; A phenylboronic acid-modified gelatin solution is prepared, and an insulin solution is prepared; the phenylboronic acid-modified gelatin solution is added dropwise to the insulin solution, and stirred at a stirring speed of 400-800 rpm for 20-40 min to obtain a polyelectrolyte complex formed by the phenylboronic acid-modified gelatin and insulin; The polyelectrolyte complex formed by phenylboronic acid-modified gelatin and insulin is mixed with an equal volume of 1 mg / mL L-valine-chitosan solution, and stirred at a stirring speed of 400-800 rpm for 10-30 min to obtain a nanoparticle complex; An equal volume of a fucoidan solution with a concentration of 2 mg / mL is added to the nanocomplex, stirred at a stirring speed of 400-800 rpm for 10-30 min, and then centrifuged at a centrifugal speed of 4000 rpm for 15-30 min; finally, the supernatant is taken to obtain composite nanoparticles with a multilayer core-shell structure double-modified with phenylboronic acid and L-valine loaded with insulin, that is, composite nanoparticles loaded with insulin.

8. The method for preparing insulin-loaded composite nanoparticles according to claim 7, characterized in that: The preparation process of phenylboronic acid modified gelatin solution is as follows: Pure water and DMSO were mixed in a volume ratio of 1:4 to form a mixed solvent, gelatin was added to the mixed solvent, 40 mg of gelatin was added to each milliliter of the mixed solvent, the pH was adjusted to 5 with HCl, and then heated to dissolve; Then, amino-substituted phenylboronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and N-hydroxysuccinimide were dissolved in a mixed solution of pure water and DMSO at a molar ratio of 7:1.2:1.2, wherein the volume ratio of pure water to DMSO in the mixed solution was 1:4, and the pH was adjusted to 5 with HCl; The mixed solution containing gelatin is mixed with a mixed solution containing amino-substituted phenylboronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, stirred at room temperature for 48 hours, and then placed in a dialysis bag for dialyzing for one week. After the dialysis is completed, the mixture is freeze-dried to obtain phenylboronic acid-modified gelatin; The phenylboronic acid-modified gelatin was dissolved in deionized water to prepare a phenylboronic acid-modified gelatin solution with a concentration of 1 mg / mL, and the pH was adjusted to 4.

9. The method for preparing insulin-loaded composite nanoparticles according to claim 8, characterized in that: The amino-substituted phenylboronic acid is any one of 4-aminophenylboronic acid, 3-aminophenylboronic acid, 3-fluoro-4-aminophenylboronic acid and 3-nitro-4-aminophenylboronic acid.

10. Use of the insulin-loaded composite nanoparticles as claimed in claim 6 for oral administration and injection for the treatment of diabetes.